AC / CeO2 / ZnMn2O4 composite photocatalyst as well as preparation method and application thereof

By preparing AC/CeO2/ZnMn2O4 composite photocatalyst, and using ultrasonic treatment technology to recombine activated carbon with CeO2/ZnMn2O4 heterojunction photocatalyst, the problems of low degradation efficiency of tannin acid and secondary contamination of adsorbents in the prior art are solved, and the problem of low tannin acid degradation efficiency and secondary contamination of adsorbents are achieved. Efficient and stable tannin removal and recycling.

CN119425669AActive Publication Date: 2025-02-14CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411396347.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-14
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently degrade tannin acid, and the adsorbent is prone to secondary pollution after use and lacks recycling ability.

Method used

AC/CeO2/ZnMn2O4 composite photocatalyst was prepared, and activated carbon and CeO2/ZnMn2O4 heterojunction photocatalyst were combined by sonication to form a composite material with a large specific surface area and pore volume.

Benefits of technology

High-efficiency photocatalytic degradation of tannin acid is achieved, with good stability and recycling properties, and can significantly improve the removal rate during the removal of tannin acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425669A_ABST
    Figure CN119425669A_ABST
Patent Text Reader

Abstract

The invention discloses an AC / CeO2 / ZnMn2O4 composite photocatalyst as well as a preparation method and application of the AC / CeO2 / ZnMn2O4 composite photocatalyst. The AC / CeO2 / ZnMn2O4 composite photocatalyst is prepared from AC, CeO2 and ZnMn2O4, the mass ratio of the CeO2 to the ZnMn2O4 is (0.25 to 1) to 1, and the mass ratio of the AC to the CeO2 / ZnMn2O4 is (0.1 to 1) to (0.5 to 1). The AC / CeO2 / ZnMn2O4 composite photocatalyst is prepared by the following three steps: firstly, preparing long-strip-shaped ZnMn2O4 by adopting a coprecipitation-calcination method, then adding a cerous nitrate solution to uniformly disperse the long-strip-shaped ZnMn2O4, obtaining a precipitate mixture under the precipitation action of ammonia water, pyrolyzing to obtain CeO2 / ZnMn2O4, and finally, compounding AC and CeO2 / ZnMn2O4 by adopting an ultrasonic treatment process to obtain the AC / CeO2 / ZnMn2O4 composite photocatalyst. The composite photocatalyst is combined with traditional adsorption and photocatalysis processes, and has high photocatalytic degradation efficiency and reaction stability on tannic acid under simulated sunlight illumination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to an AC / CeO2 / ZnMn2O4 composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Numerous adsorbents such as activated carbon, zeolite, bentonite and silica have been used to remove many pollutants, including heavy metals and organic compounds from industrial wastewater. The adsorption method has the characteristics of simplicity, low toxicity, cost-effectiveness and easy combination with other methods, which has attracted a large number of scholars to develop this technology. For example, the excess tannic acid used to recover germanium in the hydrometallurgical zinc smelting process is removed by activated carbon adsorption. However, this method can only adsorb a certain amount of tannic acid, and cannot achieve the effect of degrading tannic acid and reusing it, and it is even easy to form secondary pollution after use. In recent years, due to the advantages of cleanliness and high efficiency shown by photocatalytic technology in the degradation of organic matter, it has also attracted great attention from more and more researchers. Summary of the invention

[0003] In order to solve the technical problems and shortcomings in the prior art, the object of the present invention is to provide a composite photocatalyst that can efficiently degrade tannic acid and has recycling capability.

[0004] To achieve the above object, the technical solution of the present invention is as follows:

[0005] In a first aspect, the present invention provides a method for preparing an AC / CeO2 / ZnMn2O4 composite photocatalyst, comprising the following steps:

[0006] (1) Preparation of ZnMn2O4:

[0007] Add zinc acetate (CH3COO)2Zn·2H2O and manganese acetate (CH3COO)2Mn·4H2O into ethanol-water solution and stir until completely dissolved to obtain solution A;

[0008] Add oxalic acid H2C2O4·2H2O to ethanol-water solution and stir until completely dissolved to obtain solution B;

[0009] The solution A is quickly poured into the solution B, heated and stirred to obtain a mixed solution, and after the mixed solution is cooled to room temperature, it is filtered, washed and dried to obtain a precursor A;

[0010] Precursor A is placed in a tube furnace for high-temperature calcination to obtain ZnMn2O4 in the form of long strips;

[0011] (2) Preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst:

[0012] The ZnMn2O4 obtained in step (1) is added to the cerium nitrate solution, and stirred thoroughly to be uniformly dispersed in the cerium nitrate solution; then 25% ammonia water is added dropwise, heated and stirred to obtain a precipitated mixture, and after the reaction, the precipitated mixture is cooled to room temperature, and the precipitated mixture is filtered, washed and dried to obtain a precursor B, and the precursor B is placed in a tube furnace for high-temperature calcination to obtain a CeO2 / ZnMn2O4 heterojunction photocatalyst;

[0013] (3) Preparation of AC / CeO2 / ZnMn2O4 composite photocatalyst:

[0014] Activating the activated carbon using an alkaline solution;

[0015] The CeO2 / ZnMn2O4 heterojunction photocatalyst obtained in step (2) is added into deionized water and stirred and dispersed thoroughly, then alkali-activated activated carbon AC is added and stirred thoroughly, the mixed solution is ultrasonically treated at 35-45 kHz and an ultrasonic power of 150-180 W for 1-1.5 hours, the ultrasonically treated suspension is filtered, washed and dried to obtain an AC / CeO2 / ZnMn2O4 composite photocatalyst; wherein the mass ratio of alkali-activated activated carbon AC to CeO2 / ZnMn2O4 heterojunction photocatalyst is 0.1:1-0.5:1.

[0016] Preferably, in step (1), the volume ratio of ethanol to water in the ethanol-water solution is 9:1.

[0017] The volume ratio of ethanol to water in the precipitation medium plays a key role in the change of the aspect ratio of the ZnMn2O4 particles. By adopting the preferred embodiment of the above step (1), a long strip of porous ZnMn2O4 with a large specific surface area and pore volume can be prepared, which is conducive to the full contact between the photocatalyst and the degradation target, and provides more mass transfer channels and reaction active sites, reduces the recombination rate of photogenerated electrons and holes, and improves the photocatalytic degradation efficiency.

[0018] Preferably, in step (1), the total metal ion concentration of zinc and manganese in the solution A is 0.02 to 0.16 mol / L.

[0019] Preferably, in step (1), the molar ratio of zinc acetate to manganese acetate is 1:2, and the molar ratio of oxalic acid to zinc acetate is 3-3.6:1.

[0020] Preferably, in step (1), the heating and stirring are performed at a heating temperature of 50 to 60° C., a stirring rate of 500 to 1000 r / min, and a stirring time of 2 to 2.5 h.

[0021] Preferably, in step (1) and step (2), the precursor A and the precursor B are heated to 450-550° C. at a heating rate of 2-10° C. / min for calcination, and the calcination holding time is 2-2.5 h.

[0022] The heating rate, calcination temperature and calcination time of step (1) and step (2) are the same.

[0023] Preferably, in step (2), the concentration of the cerium nitrate solution is 3.0-7.5 mmol / L, the amount of ZnMn2O4 added is 1.25-2 g / L, and the volume ratio of the 25% ammonia water added to the cerium nitrate solution is 0.01-1:40.

[0024] Preferably, in step (2), the heating and stirring are performed at a heating temperature of 40 to 50° C., a stirring rate of 500 to 700 r / min, and a stirring time of 2 to 2.5 h.

[0025] Preferably, in step (3), the mass volume ratio (g / mL) of the activated carbon and the alkaline solution is 1:5 to 1:4, and the alkaline solution is a KOH solution with a concentration of 1% to 5% (w / w).

[0026] As an exemplary illustration, the specific operation of step (3) is as follows:

[0027] Commercial activated carbon is added to a potassium hydroxide (KOH) solution of a certain volume concentration, stirred and mixed at room temperature for a period of time, filtered, and continuously washed with dilute hydrochloric acid and distilled water to make the pH of the activated carbon filtrate neutral, and then dried overnight to obtain alkali-activated AC; the CeO2 / ZnMn2O4 heterojunction photocatalyst in step (2) is added to deionized water (mass volume ratio is 0.1:30-0.1:20) and stirred and dispersed for 10-20 minutes, and then alkali-activated AC with a mass ratio of 0.1-1:2 to the CeO2 / ZnMn2O4 heterojunction photocatalyst is added and stirred for 20-30 minutes, and mixed with the above CeO2 / ZnMn2O4 suspension. Next, the mixed solution is ultrasonically treated at 35-45kHz with an ultrasonic power of 150-180W for 1-1.5 hours. Finally, the ultrasonically treated suspension is filtered, washed, and dried to obtain an AC / CeO2 / ZnMn2O4 composite photocatalyst.

[0028] In a second aspect, the present invention provides an AC / CeO2 / ZnMn2O4 composite photocatalyst material prepared by the aforementioned preparation method, wherein the mass ratio of CeO2 and ZnMn2O4 is 0.25 to 1:1, and the mass ratio of AC and CeO2 / ZnMn2O4 is 0.1:1 to 0.5:1.

[0029] In a third aspect, the present invention provides the use of the aforementioned AC / CeO2 / ZnMn2O4 composite photocatalyst material in photocatalytic degradation of tannic acid.

[0030] Compared with the prior art, the beneficial effects of the technical solution of the present invention at least include:

[0031] (1) The AC / CeO2 / ZnMn2O4 composite photocatalyst prepared by the present invention has a large specific surface area, excellent visible light response ability and photocatalytic activity, can efficiently adsorb and photodegrade tannic acid, and has better photocatalytic degradation performance than pure ZnMn2O4 and CeO2 / ZnMn2O4 photocatalysts.

[0032] (2) The AC / CeO2 / ZnMn2O4 composite photocatalyst prepared by the present invention has good stability and recyclability.

[0033] (3) The AC / CeO2 / ZnMn2O4 composite photocatalyst prepared by the present invention shows a high removal rate of tannic acid by combining adsorption and photocatalytic reaction processes, wherein AC plays a key role as a transfer path for charge carriers and a "bridge" between tannic acid and the catalyst. The composite photocatalyst has good practical value and potential application prospects in removing tannic acid from zinc leachate. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 These are the field scanning electron microscope photograph (a), SEM picture (b), C, Mn, Ce, Zn element distribution diagram (cf), and X-ray diffraction patterns (g) of AC, CeO2 / ZnMn2O4 and AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1.

[0035] Figure 2 This is a field scanning electron microscope photograph of the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1.

[0036] Figure 3 This is the UV-visible diffuse reflectance spectrum of the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1.

[0037] Figure 4 It is the nitrogen adsorption-desorption curve and pore size distribution diagram of the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1.

[0038] Figure 5 This is the curve of tannic acid concentration variation over time in the photocatalytic degradation reaction of the samples prepared in Examples 1 to 3.

[0039] Figure 6This is a bar chart of the cyclic stability of the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1. DETAILED DESCRIPTION

[0040] The objectives, specific implementation methods and advantages of the present invention are described in detail below, but the present invention is not limited to the following description.

[0041] The present invention composites AC and CeO2 / ZnMn2O4 heterojunction photocatalysts to construct an AC / CeO2 / ZnMn2O4 composite photocatalyst. The material exhibits enhanced visible light absorption capacity and photogenerated electron-hole separation efficiency, improves the photocatalytic efficiency of tannic acid, and has excellent recycling performance, which is of great significance for the application of photocatalytic removal of tannic acid in zinc leachate.

[0042] The technical solution of the present invention is described below in conjunction with specific embodiments:

[0043] Comparative Example 1:

[0044] The preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst includes the following steps:

[0045] (1) Preparation of ZnMn2O4:

[0046] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain solution A. Similarly, 0.378g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain solution B. Solution A was then quickly poured into solution B, and the mixture was stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a tubular furnace for calcination, and kept at 450°C for 2h at a heating rate of 2°C / min to finally obtain ZnMn2O4 with a long strip morphology.

[0047] (2) Preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst:

[0048] 100 mg of cerium nitrate is added to 40 mL of deionized water and stirred until completely dissolved; then 60 mg of ZnMn2O4 obtained in step (1) is added to the above cerium nitrate solution and stirred thoroughly to make it evenly dispersed in the cerium nitrate solution; then 0.8 mL of 25% ammonia water is added dropwise, stirred at 40°C and 700 r / min for 2 hours, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60°C overnight; finally, the dried precursor is placed in a tubular furnace and kept at 450°C for 2 hours at a heating rate of 2°C / min to obtain a CeO2 / ZnMn2O4 heterojunction photocatalyst.

[0049] Embodiment 1:

[0050] An AC / CeO2 / ZnMn2O4 composite photocatalyst is prepared by the following preparation steps:

[0051] (1) Preparation of ZnMn2O4:

[0052] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain solution A. Similarly, 0.378g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain solution B. Solution A was then quickly poured into solution B, and the mixture was stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a tubular furnace for calcination, and kept at 450°C for 2h at a heating rate of 2°C / min to finally obtain ZnMn2O4 with a long strip morphology.

[0053] (2) Preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst:

[0054] 100 mg of cerium nitrate is added to 40 mL of deionized water and stirred until completely dissolved; then 60 mg of ZnMn2O4 obtained in step (1) is added to the above cerium nitrate solution and stirred thoroughly to make it evenly dispersed in the cerium nitrate solution; then 0.8 mL of 25% ammonia water is added dropwise, stirred at 40°C and 700 r / min for 2 hours, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60°C overnight; finally, the dried precursor is placed in a tubular furnace and kept at 450°C for 2 hours at a heating rate of 2°C / min to obtain a CeO2 / ZnMn2O4 heterojunction photocatalyst.

[0055] (3) AC / CeO2 / ZnMn2O4 composite photocatalyst

[0056] 25g AC was added to 100mL 1% KOH solution, stirred continuously for 24h at room temperature, filtered, and washed continuously with dilute hydrochloric acid and distilled water to make the pH of AC filtrate neutral, and then dried overnight to obtain alkali-activated AC; 0.10g CeO2 / ZnMn2O4 heterojunction photocatalyst was added to 20mL deionized water and fully stirred and dispersed for 10 to 20 minutes, and then 0.03g alkali-activated AC was added and stirred continuously for 20 to 30 minutes, and mixed with the above CeO2 / ZnMn2O4 suspension. Next, the mixed solution was ultrasonically treated at 45kHz with an ultrasonic power of 180W for 1 hour. Finally, the ultrasonically treated suspension was filtered, washed, and dried to obtain AC / CeO2 / ZnMn2O4 composite photocatalyst.

[0057] The X-ray diffraction patterns and EDX elemental analysis scans of the samples obtained in Example 1 of the present invention and Comparative Example 1 are shown in Figure 1 . The X-ray diffraction pattern shows that both the CeO2 / ZnMn2O4 composite material and the AC / CeO2 / ZnMn2O4 composite photocatalyst have obvious CeO2 and ZnMn2O4 characteristic peaks; the EDX elemental analysis scan shows that the middle layer of the long block AC / CeO2 / ZnMn2O4 composite photocatalyst only shows C and O elements, and Ce, Zn and Mn elements are evenly distributed on the surface of the AC / CeO2 / ZnMn2O4 composite photocatalyst, indicating that the CeO2 / ZnMn2O4 particles are relatively evenly distributed on the AC surface. In summary, Example 1 of the present invention prepared an AC / CeO2 / ZnMn2O4 composite photocatalyst with high purity.

[0058] The field scanning electron microscope photo of the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1 of the present invention is shown in detail. Figure 2 ,Depend on Figure 2 It can be seen that a large number of tiny spherical CeO2 / ZnMn2O4 particles are aggregated on the surface of the AC / CeO2 / ZnMn2O4 composite photocatalyst. The distribution of CeO2 / ZnMn2O4 photocatalyst particles on the surface of the AC / CeO2 / ZnMn2O4 composite photocatalyst produces more pore structures and provides more active sites, thereby improving the adsorption and photocatalytic capabilities and effectively removing tannic acid.

[0059] The UV-visible diffuse reflectance spectrum of the sample prepared in Example 1 of the present invention is shown in detail. Figure 3 ,Depend on Figure 3It can be seen that the AC / CeO2 / ZnMn2O4 composite photocatalyst has significantly enhanced absorption in the visible light range of 400-800nm ​​compared with ZnMn2O4 and CeO2 / ZnMn2O4 heterojunction photocatalysts, which is beneficial to the photocatalytic reaction under visible light.

[0060] The nitrogen adsorption and desorption curve of the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Example 1 of the present invention is shown in detail. Figure 4 ,Depend on Figure 4 It can be seen that the adsorption-desorption curve of AC / CeO2 / ZnMn2O4 composite material is a type IV isotherm, and the adsorption hysteresis loop belongs to the H3 type, indicating that the sample has a mesoporous structure. AC / CeO2 / ZnMn2O4 has a large specific surface area and pore volume, which are 111.842m 2 ·g -1 and 0.176cm 3 ·g -1 , providing a large number of surface active sites for photocatalytic reactions, which is beneficial to the improvement of adsorption and photocatalytic efficiency.

[0061] Embodiment 2:

[0062] An AC / CeO2 / ZnMn2O4 composite photocatalyst is prepared by the following preparation steps:

[0063] (1) Preparation of ZnMn2O4:

[0064] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain solution A. Similarly, 0.378g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain solution B. Solution A was then quickly poured into solution B, and the mixture was stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a tubular furnace for calcination, and kept at 450°C for 2h at a heating rate of 2°C / min to finally obtain ZnMn2O4 with a long strip morphology.

[0065] (2) Preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst:

[0066] 100 mg of cerium nitrate is added to 40 mL of deionized water and stirred until completely dissolved; then 60 mg of ZnMn2O4 obtained in step (1) is added to the above cerium nitrate solution and stirred thoroughly to make it evenly dispersed in the cerium nitrate solution; then 0.8 mL of 25% ammonia water is added dropwise, stirred at 40°C and 700 r / min for 2 hours, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60°C overnight; finally, the dried precursor is placed in a tubular furnace and kept at 450°C for 2 hours at a heating rate of 2°C / min to obtain a CeO2 / ZnMn2O4 heterojunction photocatalyst.

[0067] (3) AC / CeO2 / ZnMn2O4 composite photocatalyst

[0068] Add 25g AC to 100mL 1% KOH solution, stir continuously for 24h at room temperature, filter, wash with dilute hydrochloric acid and distilled water continuously to make the pH of AC filtrate neutral, and then dry overnight to obtain alkali-activated AC; take 0.10g CeO2 / ZnMn2O4 heterojunction photocatalyst, add it to 20mL deionized water and stir and disperse it for 10 to 20 minutes, then add 0.01g alkali-activated AC and continue stirring for 20 to 30 minutes, and mix it with the above CeO2 / ZnMn2O4 suspension. Next, the mixed solution is ultrasonically treated at 45kHz with an ultrasonic power of 180W for 1 hour. Finally, the ultrasonically treated suspension is filtered, washed, and dried to obtain AC / CeO2 / ZnMn2O4 composite photocatalyst.

[0069] Embodiment 3:

[0070] An AC / CeO2 / ZnMn2O4 composite photocatalyst is prepared by the following preparation steps:

[0071] (1) Preparation of ZnMn2O4:

[0072] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain solution A. Similarly, 0.378g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (45mL+5mL), and the mixture was stirred until completely dissolved to obtain solution B. Solution A was then quickly poured into solution B, and the mixture was stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was placed in a porcelain boat and placed in a tubular furnace for calcination, and the mixture was kept at 450°C for 2h at a heating rate of 2°C / min to finally obtain ZnMn2O4 with a long strip morphology.

[0073] (2) Preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst:

[0074] 100 mg of cerium nitrate is added to 40 mL of deionized water and stirred until completely dissolved; then 60 mg of ZnMn2O4 obtained in step (1) is added to the above cerium nitrate solution and stirred thoroughly to make it evenly dispersed in the cerium nitrate solution; then 0.8 mL of 25% ammonia water is added dropwise, stirred at 40°C and 700 r / min for 2 hours, cooled to room temperature, filtered and collected the mixed precipitate, washed with deionized water and ethanol three times, and dried in an oven at 60°C overnight; finally, the dried precursor is placed in a tubular furnace and kept at 450°C for 2 hours at a heating rate of 2°C / min to obtain a CeO2 / ZnMn2O4 heterojunction photocatalyst.

[0075] (3) AC / CeO2 / ZnMn2O4 composite photocatalyst

[0076] 25g AC was added to 100mL 1% KOH solution, stirred continuously for 24h at room temperature, filtered, and washed continuously with dilute hydrochloric acid and distilled water to make the pH of AC filtrate neutral, and then dried overnight to obtain alkali-activated AC; 0.10g CeO2 / ZnMn2O4 heterojunction photocatalyst was added to 20mL deionized water and fully stirred and dispersed for 10 to 20 minutes, and then 0.05g alkali-activated AC was added and stirred continuously for 20 to 30 minutes, and mixed with the above CeO2 / ZnMn2O4 suspension. Next, the mixed solution was ultrasonically treated at 45kHz with an ultrasonic power of 180W for 1 hour. Finally, the ultrasonically treated suspension was filtered, washed, and dried to obtain AC / CeO2 / ZnMn2O4 composite photocatalyst.

[0077] Application examples:

[0078] The CeO2 / ZnMn2O4 heterojunction photocatalyst prepared in Comparative Example 1 and the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Examples 1 to 3 were used to catalytically degrade tannic acid under simulated solar illumination.

[0079] The specific operations are as follows:

[0080] (1) Control group: 50 mL of 200 mg·L -1 The samples were treated with tannic acid solution in the dark for 30 minutes and then irradiated under a xenon lamp for 150 minutes.

[0081] (2) CeO2 / ZnMn2O4 group: 20 mg of the CeO2 / ZnMn2O4 heterojunction photocatalyst prepared in Comparative Example 1 was weighed and added to a quartz test tube, and then 50 mL of 200 mg·L -1The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then the xenon lamp was turned on to carry out photocatalytic reaction under simulated sunlight. 2 mL of the reaction solution sample was taken every 30 minutes, and the solution was filtered with a 0.22 μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the reduction rate.

[0082] (3) AC / CeO2 / ZnMn2O4 group: 20 mg of the AC / CeO2 / ZnMn2O4 photocatalyst prepared in Example 1 was weighed and added to a quartz test tube, and then 50 mL of 200 mg·L -1 The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then the xenon lamp was turned on to carry out photocatalytic reaction under simulated sunlight. 2 mL of the reaction solution sample was taken every 30 minutes, and the solution was filtered with a 0.22 μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the reduction rate.

[0083] Application Example 1:

[0084] Tannic acid was photocatalytically degraded under simulated solar light using a tannic acid solution without any catalyst added (control), ZnMn2O4, the CeO2 / ZnMn2O4 heterojunction photocatalyst prepared in Comparative Example 1, and the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Examples 1 to 3.

[0085] Weigh 20 mg of the sample to be tested and add it to a quartz test tube, then measure 50 mL of 200 mg·L -1 The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then a 500w xenon lamp was turned on to carry out a photocatalytic reaction under simulated sunlight. 2mL of the reaction solution sample was taken at fixed intervals, and the solution was filtered with a 0.22μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the reduction rate (see Table 1).

[0086] Table 1. Photodegradation rate of tannic acid in Examples 1-3

[0087] Time (min) Comparison <![CDATA[ZnMn2O4]]> Comparative Example 1 Example 1 Example 2 Example 3 -30(dark reaction) 0% 0% 0% 0% 0% 0% 0 0.1% 46.7% 62.4% 68.1% 70.0% 64.8% 15 0.3% 55.8% 80.3% 89.9% 82.8% 84.18% 30 0.4% 64.4% 89.1% 96.0% 95.6% 97.18% 45 0.5% 70.8% 98.4% 98.2% 98.2% 98.7% 60 0.6% 76.7% 99.0% 100% 99.6% 99.3%

[0088] Depend on Figure 5It can be seen that during the dark adsorption process, the photocatalytic removal rate of tannic acid by the CeO2 / ZnMn2O4 heterojunction photocatalyst prepared in Comparative Example 1 is 99% within 60 minutes, and the photocatalytic removal rates of tannic acid by the AC / CeO2 / ZnMn2O4 composite photocatalyst prepared in Examples 1 to 3 can reach 100%, 99.6% and 99.3% respectively within 60 minutes, indicating that the AC / CeO2 / ZnMn2O4 composite photocatalysis combined with the adsorption and photocatalytic reaction process shows an efficient removal rate for tannic acid, among which AC plays a key role as a transfer path for charge carriers and a "bridge" between tannic acid and the catalyst.

[0089] Application Example 2:

[0090] The AC / CeO2 / ZnMn2O4 composite photocatalyst of the first photoreaction in Application Example 1 was centrifuged and dried to obtain the AC / CeO2 / ZnMn2O4 composite photocatalyst of the first cycle, and then the AC / CeO2 / ZnMn2O4 composite photocatalyst of the first cycle was added to 50 mL of 200 mg·L -1 The tannic acid solution was poured into a quartz test tube containing the catalyst, and then ultrasonically dispersed for 5 minutes and then dark treated for 30 minutes to allow the catalyst to reach adsorption equilibrium. Then a 500w xenon lamp was turned on, and the photocatalytic reaction was carried out under simulated sunlight for 60 minutes. After that, the reduction rate was calculated as the first cycle degradation rate. This was repeated four times. The degradation rates of each cycle were as follows: Figure 6 As shown. Figure 6 It can be seen that after four cycles, the degradation rate of tannic acid by AC / CeO2 / ZnMn2O4 composite photocatalyst is still 86.6%, indicating that it has good cycle stability.

[0091] The above examples only express several preferred implementations of the present invention, and the detailed description cannot be understood as limiting the scope of the present invention. Under the premise of not departing from the technical concept and characteristics of the present invention, all modifications and equivalent modifications made according to the present invention belong to the protection scope of the present invention.

Claims

1. A method for preparing an AC / CeO2 / ZnMn2O4 composite photocatalyst, characterized in that: The following steps are involved: (1) Preparation of ZnMn2O4: Add zinc acetate (CH3COO)2Zn·2H2O and manganese acetate (CH3COO)2Mn·4H2O into ethanol-water solution and stir until completely dissolved to obtain solution A; Add oxalic acid H2C2O4·2H2O to ethanol-water solution and stir until completely dissolved to obtain solution B; The solution A is quickly poured into the solution B, heated and stirred to obtain a mixed solution, and after the mixed solution is cooled to room temperature, it is filtered, washed and dried to obtain a precursor A; The precursor A is calcined to obtain ZnMn2O4 with a long strip morphology; (2) Preparation of CeO2 / ZnMn2O4 heterojunction photocatalyst: The ZnMn2O4 obtained in step (1) is added to the cerium nitrate solution, and stirred thoroughly to be uniformly dispersed in the cerium nitrate solution; then 25% ammonia water is added dropwise, heated and stirred to obtain a precipitated mixture, and after the reaction, the precipitated mixture is cooled to room temperature, filtered, washed and dried to obtain a precursor B, and the precursor B is calcined to obtain a CeO2 / ZnMn2O4 heterojunction photocatalyst; (3) Preparation of AC / CeO2 / ZnMn2O4 composite photocatalyst: Activating the activated carbon using an alkaline solution; The CeO2 / ZnMn2O4 heterojunction photocatalyst obtained in step (2) Add deionized water and stir to disperse, then add alkali-activated activated carbon AC and stir to disperse, ultrasonically treat the mixed solution at 35-45kHz with an ultrasonic power of 150-180W for 1-1.5 hours, filter, wash and dry the ultrasonically treated suspension to obtain AC / CeO2 / ZnMn2O4 composite photocatalyst; Wherein, the mass ratio of alkali-activated activated carbon AC and CeO2 / ZnMn2O4 composite material is 0.1:1-0.5:

1.

2. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to water in the ethanol-water solution is 9:

1.

3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of zinc acetate to manganese acetate is 1:2, and the molar ratio of oxalic acid to zinc acetate is 3-3.6:

1.

4. The preparation method according to claim 1, characterized in that: In step (1), the metal ion concentration in the solution A is 0.02-0.16 mol / L.

5. The preparation method according to claim 1, characterized in that: In step (1), the heating and stirring are performed at a temperature of 50 to 60° C., a stirring rate of 500 to 1000 r / min, and a stirring time of 2 to 2.5 h.

6. The preparation method according to claim 1, characterized in that: In step (1) and step (2), the precursor A and the precursor B are heated to 450-550° C. at a heating rate of 2-10° C. / min for calcination, and the calcination holding time is 2-2.5 hours.

7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the cerium nitrate solution is 3.0-7.5 mmol / L, the amount of ZnMn2O4 added is 1.25-2 g / L, and the volume ratio of the 25% ammonia water added to the cerium nitrate solution is 0.01-1:

40.

8. The preparation method according to claim 1, characterized in that: In step (2), the heating and stirring are performed at a temperature of 40 to 50° C., a stirring rate of 500 to 700 r / min, and a stirring time of 2 to 2.5 h.

9. The preparation method according to claim 1, characterized in that: In step (3), the mass volume ratio (g / mL) of the activated carbon and the alkaline solution is 1:5 to 1:4, and the alkaline solution is a KOH solution with a concentration of 1% to 5% (w / w).

10. An AC / CeO2 / ZnMn2O4 composite photocatalyst material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9, wherein the mass ratio of CeO2 to ZnMn2O4 is 0.25 to 1:1, and the mass ratio of AC to CeO2 / ZnMn2O4 is 0.1:1 to 0.5:

1.

11. Use of the AC / CeO2 / ZnMn2O4 composite photocatalyst material according to claim 10 in photocatalytic degradation of tannic acid.

Citation Information

Patent Citations

  • Spherical cerium oxide powder with uniform morphology and controllable granularity as well as preparation method and application thereof

    CN111592030A

  • Efficient flue gas denitration catalyst and preparation method thereof

    CN114377688A

  • ZnMn2O4 hollow nano material as well as preparation method and application thereof

    CN116924475A